2022
DOI: 10.1007/978-3-031-20062-5_21
|View full text |Cite
|
Sign up to set email alerts
|

Learning Self-prior for Mesh Denoising Using Dual Graph Convolutional Networks

Abstract: This study presents a self-prior-based mesh inpainting framework that requires only an incomplete mesh as input, without the need for any training datasets. Additionally, our method maintains the polygonal mesh format throughout the inpainting process without converting the shape format to an intermediate, such as a voxel grid, a point cloud, or an implicit function, which are typically considered easier for deep neural networks to process. To achieve this goal, we introduce two graph convolutional networks (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…We have selected the latest representative methods for comparison, traditional methods (L0$L_0$ [HS13], GNF [ZDZ*15]) and data‐driven deep learning methods (CNR [WLT16], DNF [LLZ*20] FGC [AFB20], GeoBi [ZSW*22], DDMP [HYOS22], GCN [SFD*22]), thanks to the open‐source executable program or code provided by these authors. For the sake of fairness, all the experiments are conducted according to the parameters provided by the author or adjusted to the best performance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have selected the latest representative methods for comparison, traditional methods (L0$L_0$ [HS13], GNF [ZDZ*15]) and data‐driven deep learning methods (CNR [WLT16], DNF [LLZ*20] FGC [AFB20], GeoBi [ZSW*22], DDMP [HYOS22], GCN [SFD*22]), thanks to the open‐source executable program or code provided by these authors. For the sake of fairness, all the experiments are conducted according to the parameters provided by the author or adjusted to the best performance.…”
Section: Methodsmentioning
confidence: 99%
“…Visual comparison between ours and state‐of‐the‐art algorithms on real scanned meshes (Boy01 and Cone22) of Kinect V2. (a) Noisy, (b) GNF [ZDZ*15], (c) CNR [WLT16], (d) FGC [AFB20], (e) DDMP [HYOS22], (f) GCN [SFD*22], (g) Geobi [ZSW*22], (h) CDMS‐Net (Ours), (i) Ground truth.…”
Section: Methodsmentioning
confidence: 99%
“…Smoothness term for facet normals: As Mataev et al [21] reported, the regularization term defined with denoised output can prevent the DIP's neural network from overfitting to noise. In geometry processing, Hattori et al [54] reported a similar finding that facet normal regularization using bilateral normal filtering (BNF) [60] is effective in preserving sharp geometric features such as edges and corners. Following those studies, we introduce a regularizer as the smoothness term for facet normals:…”
Section: Data Term For Vertex Positionsmentioning
confidence: 98%
“…For techniques for meshes, Hattori et al [54] applied the self-prior to mesh restoration but only focused on mesh denoising. Thus, the self-prior for mesh inpainting has not been sufficiently investigated.…”
Section: Compute Lossesmentioning
confidence: 99%
See 1 more Smart Citation